Understanding the entrepreneurial intention among international students in Turkey - Berto Usman; Yennita (Journal of Global Entrepreneurship Research, 2019)
This paper sets out to ascertain and to revisit the concept of Entrepreneurial Intention (EI) among international students in Turkey. By utilizing Ajzen's theory of planned behavior (TPB) as the explaining model, this paper shows that EI obviously exists among the international students in Turkey. In particular, the respondents were determined by using simple random sampling method. Hereby, self-administered online questionnaires were delivered to several social media platform groups, such as WhatsApp, e-mail, Messenger, and Facebook groups of international students who recently study in 12 big cities and 25 universities across Turkey. By employing correlation, descriptive statistics, and structural analysis, the results notify that Personal Attitude (PA) and Subjective Norm (SN) of international students in Turkey generally show high mean scores. Otherwise, the Perceived Behavioral Control (PBC) performs neither high nor low mean score. Furthermore, the structural test output by utilizing SmartPLS3 indicates that PA and PBC statistically perform significant and positive direct effect on EI. Whilst, on the other hand, SN does not appear to statistically contribute to the variation of EI.
Keywords: 650; Entrepreneurial intention; Personal attitude; Subjective norm; Perceived behavioral control